2016
DOI: 10.1590/2317-1782/20162015104
|View full text |Cite
|
Sign up to set email alerts
|

Margens de tolerância e valores de referência para os formantes de vogais orais para uso em terapias de voz para surdos em computador comercial

Abstract: RESUMO Objetivo Este trabalho apresenta as margens de tolerâncias mínimas e máximas para as frequências dos três primeiros formantes (F1, F2 e F3) na pronúncia das vogais orais do português brasileiro para utilização em terapias de voz para surdos. Método As frequências foram obtidas a partir da colaboração voluntária de 53 indivíduos adultos que tiveram as vozes gravadas e convertidas em sinais digitais durante a emissão de cada uma das sete vogais (/a/, /e/, /Ɛ/, /i/, /o/, /ᴐ/, /u/), de maneira sustentada po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The next step was to estimate the number of coefficients for each data windowed, aiming to extract the pitch and the formant frequencies of the signal via LPC [33]. Then, the frequencies were obtained according to the minimal frequency criteria (according to the windowing stage of the signal) and to the maximum acceptable bandwidth [26]. The frequencies that matched both criteria were considered, the first being pitch (F0) , and the subsequent being F1 to F4 .…”
Section: Proposed Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The next step was to estimate the number of coefficients for each data windowed, aiming to extract the pitch and the formant frequencies of the signal via LPC [33]. Then, the frequencies were obtained according to the minimal frequency criteria (according to the windowing stage of the signal) and to the maximum acceptable bandwidth [26]. The frequencies that matched both criteria were considered, the first being pitch (F0) , and the subsequent being F1 to F4 .…”
Section: Proposed Methodsmentioning
confidence: 99%
“…The frequencies that matched both criteria were considered, the first being pitch (F0) , and the subsequent being F1 to F4 . In the literature, it was demonstrated that these are liable to encompass the spectral information regarding each vowel [26]. However, the developed software runs on extracting the greatest possible number of formants from audio (approximately 16–20 formants).…”
Section: Proposed Methodsmentioning
confidence: 99%
See 3 more Smart Citations